Memahami Al-Qur’an Kontemporer Antara Teks, Hermeneutika Dan Kontekstualisasi Terhadap Ayat Perbudakan - Ahmad Husein (Jurnal Ulunnuha, 2020)
This article discusses the verses of slavery contained in the Koran, contemporary slavery with classical slavery is very different, slavery in the old form where one human being can be owned by another human being can be said to be extinct but the new form of slavery is now more dangerous to humanity, namely slavery of thought, slavery of property, power, independence of the State. In this case the researcher studied the slavery verse using the Rahman Double Movement theory. In the conclusion of the research, the writer found that in terms of slavery verses, the researcher found that the moral message offered by Rahman to liberate slaves gives equality to others, frees from arbitrariness and does not disturb human rights.